استخدام مدخل التعليم النشاطي Empty outlineلتنمية التحصيل الدراسي في مهارة القراءة بالمدرسة المتوسطة الإسلامية الحكومية 3 فيدي - Miswarul Abdi Aziz (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2023)
This study aims to find out the students' response to the use of the Empty outline approach in teaching the skill of reading and to measure the effectiveness of applying the Empty outline approach in teaching the skill of reading in the governmental Islamic middle school 3 Fide, and the research method used by the researcher in writing this research is the experimental research method. By Design One Group Pretest Posllest. The results of the research indicated the response of the students in teaching reading using the Empty Outline approach at the Islamic Governmental Intermediate School 3, which is comfortable and enjoyable, and they want to teach reading after using the Empty Outline Approach. The use of the Empty outline approach is effective for the development of students' academic achievement in the reading skill of the Government Islamic Intermediate School 3 Fedi. Using the Empty outline approach, it is clear that the result of the t-test -12.59 is greater than the result of the t-table which is 2.060.